HAL-2 promotes homologous pairing during Caenorhabditis elegans meiosis by antagonizing inhibitory effects of synaptonemal complex precursors. - Weibin Zhang; Natasha Miley; Michael S Zastrow; Amy J MacQueen; Aya Sato; Kentaro Nabeshima; Enrique Martinez-Perez; Susanna Mlynarczyk-Evans; Peter M Carlton; Anne M Villeneuve (PLoS Genetics)
During meiosis, chromosomes align with their homologous pairing partners and stabilize this alignment through assembly of the synaptonemal complex (SC). Since the SC assembles cooperatively yet is indifferent to homology, pairing and SC assembly must be tightly coordinated. We identify HAL-2 as a key mediator in this coordination, showing that HAL-2 promotes pairing largely by preventing detrimental effects of SC precursors (SYP proteins). hal-2 mutants fail to establish pairing and lack multiple markers of chromosome movement mediated by pairing centers (PCs), chromosome sites that link chromosomes to cytoplasmic microtubules through nuclear envelope-spanning complexes. Moreover, SYP proteins load inappropriately along individual unpaired chromosomes in hal-2 mutants, and markers of PC-dependent movement and function are restored in hal-2; syp double mutants. These and other data indicate that SYP proteins can impede pairing and that HAL-2 promotes pairing predominantly but not exclusively by counteracting this inhibition, thereby enabling activation and regulation of PC function. HAL-2 concentrates in the germ cell nucleoplasm and colocalizes with SYP proteins in nuclear aggregates when SC assembly is prevented. We propose that HAL-2 functions to shepherd SYP proteins prior to licensing of SC assembly, preventing untimely interactions between SC precursors and chromosomes and allowing sufficient accumulation of precursors for rapid cooperative assembly upon homology verification.